PENGELOLAAN FASILITAS PADA OBJEK WISATA PEMANDIAN AIR PANAS SUAMAN KABUBPATEN ROKAN HULU - Putri, Dinda Pratiska; Sulistyani, Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
This study aims to analyze facility management at the Suaman Hot Springs tourist attraction in Rokan Hulu Regency. As one of the leading natural destinations in Riau Province, Suaman Hot Springs has great potential to attract tourists but still faces several challenges in facility management. This research uses a descriptive qualitative method with data collected through observation, in-depth interviews, and documentation. The study focuses on four management functions: planning, organizing, directing, and controlling, applied to the main, supporting, and complementary facilities. The results show that while most facilities are in fairly good condition, improvements are still needed in public restrooms, parking areas, and accessibility. Major obstacles include limited budget, lack of human resources, and the absence of a formal organizational structure. Therefore, long-term planning and cross-sector collaboration between the government, tourism managers, and the community are necessary to support the sustainability of this destination. This research is expected to serve as an evaluation material and provide strategic recommendations for facility development that prioritizes visitor comfort and increased tourist visits. Keywords: Management, Facilities, Suaman Hot Spring